SYNTHESIS AND PROPERTIES OF NOVEL PT(II)-CONTAINING POLYPHOSPHAZENES - BAIK, H; JUNG, OS; SUNG, YK; SOHN, YS (KOREAN CHEMICAL SOC, 1995)
Poly(dichlorophosphazene) having low molecular weight ((M) over bar w similar to 10(4)) was synthesized by the thermal reaction of hexachlorocyclotriphosphazene in the presence of excess AlCl3 (>2%) as catalyst. Using the poly(dichlorophosphazene), poly[bis(ethylglycino)phosphazene], poly[bis(glycinemethylamido)phosphazene], and poly[(glycinemethylamido)(methyiamino)phosphazene] were prepared. Diammineplatinum(II) complex cation was introduced into these derivatized phosphazene polymers, and the resultant polymers containing the platinum(II) moiety were charaterized by means of elemental analysis, IR and NMR spectroscopies, and then subjected to in vitro and in vivo assays of antitumor activity.
Keywords: PHOSPHAZENE HIGH POLYMERS; SIDE GROUPS; AMINOPHOSPHAZENES